Graphene as a Lubricant Additive for Reducing Friction and Wear in Its Liquid-Based Form - Ab Rahman Marlinda; Gregory Soon How Thien; Mehmood Shahid; Ting Yang Ling; Abu Hashem; Kah-Yoong Chan; Mohd Rafie Johan (Lubricants, 2023)
Graphene is a single atomic plane of sp2-bound carbon that has attracted considerable interest in various technologies. On the basis of its unique physical, mechanical, and chemical properties, graphene is a potentially strong candidate as a lubricant additive in its liquid-based form to reduce friction and protect surfaces from degrading. Furthermore, graphene on wear performance acts as a heat dissipation source for liquid lubricants. This review explores and addresses the fundamental mechanisms illuminating the exceptional tribological behaviours of graphene family materials and their limitations. Although graphene additives were reported to improve friction coefficients and wear properties, several challenges remain a hindrance, such as production costs, dispersion stability, and lack of information regarding graphene optimisation. Thus, this review can provide a standard methodological framework for graphene additives in improving tribological performance. Moreover, this review provides an up-to-date review of current tribological experiments based on ultrafine particles incorporated with graphene as an additive for lubricating liquids.